Deep‐sea coral δ13C: A tool to reconstruct the difference between seawater pH and δ11B‐derived calcifying fluid pH. Issue 1 (11th January 2016) - Martin, Patrick; Goodkin, Nathalie F.; Stewart, Joseph A.; Foster, Gavin L.; Sikes, Elisabeth L.; White, Helen K.; Hennige, Sebastian; Roberts, J. Murray
Abstract: The boron isotopic composition ( δ 11 B) of coral skeleton is a proxy for seawater pH. However, δ 11 B‐based pH estimates must account for the pH difference between seawater and the coral calcifying fluid, ΔpH. We report that skeletal δ 11 B and ΔpH are related to the skeletal carbon isotopic composition ( δ 13 C) in four genera of deep‐sea corals collected across a natural pH range of 7.89–8.09, with ΔpH related to δ 13 C by ΔpH = 0.029 ×  δ 13 C + 0.929, r 2  = 0.717. Seawater pH can be reconstructed by determining ΔpH from δ 13 C and subtracting it from the δ 11 B‐derived calcifying fluid pH. The uncertainty for reconstructions is ±0.12 pH units (2 standard deviations) if estimated from regression prediction intervals or between ±0.04 and ±0.06 pH units if estimated from confidence intervals. Our new approach quantifies and corrects for vital effects, offering improved accuracy relative to an existing δ 11 B versus seawater pH calibration with deep‐sea scleractinian corals. Key Points: Skeletal δ 11 B and δ 13 C are related across four deep‐sea coral genera δ 13 C is strongly related to the difference between coral and seawater pH We propose a dual‐proxy approach to estimate seawater pH from δ 11 B and δ 13 C